1971
DOI: 10.1159/000192843
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamines in Chronic Respiratory Insufficiency

Abstract: Twelve patients with chronic respiratory failure in obstructive pulmonary emphysema had a significant increase in plasma catecholamines of about three times the normal values. It is suggested that chronic hypercapnia stimulates the sympathetic nervous system thus being partly responsible for several cardiovascular features as tachycardia, arrhythmia and increased cardiac output often observed in patients with chronic respiratory insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1972
1972
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Even moderate surgical trauma such as c holecystectomy is followed by a fall in muscle glycogen concentration to the same level as observed in the present RF group [16]. Furthermore, raised concentrations of the stress hormones adrenaline and noradrenaline have been reported in chronic RF [17]. The hypothesis can therefore be put forward that the RF situallon induces a stress reaction possibly via hypoxia which leads to a deterioration in muscle energy metabolism.…”
Section: Discussionsupporting
confidence: 76%
“…Even moderate surgical trauma such as c holecystectomy is followed by a fall in muscle glycogen concentration to the same level as observed in the present RF group [16]. Furthermore, raised concentrations of the stress hormones adrenaline and noradrenaline have been reported in chronic RF [17]. The hypothesis can therefore be put forward that the RF situallon induces a stress reaction possibly via hypoxia which leads to a deterioration in muscle energy metabolism.…”
Section: Discussionsupporting
confidence: 76%
“…The release of FFA and increase in concentration in the blood is pro moted by, amongst other things, catecholamines and steroids. Raised levels of catecholamines in blood has been reported in chronic respiratory failure [17]. If this is the case one would expect increased lipolysis with high concentrations of lipid metabolites in pa tients with CRF compared to those without.…”
Section: Discussionmentioning
confidence: 94%
“… 28 Previous studies found that COPD patients had a higher catecholamine level, possibly due to the over activation of the sympathetic nervous system (SNS) and the use of β-agonists in the treatment of COPD can also mimic the actions of sympathetic adrenergic stimulation. 21 , 22 , 29 , 30 Also, many clinical studies reported the acute exacerbation of COPD as the potential triggering factor for TCM. 21 23 TCM and COPD may share some similar underlying pathophysiology.…”
Section: Discussionmentioning
confidence: 99%